At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the quadratic equation [tex]\(-10x^2 + 12x - 9 = 0\)[/tex], we will use the quadratic formula, which is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a = -10\)[/tex], [tex]\(b = 12\)[/tex], and [tex]\(c = -9\)[/tex].
First, we calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \text{Discriminant} = 12^2 - 4(-10)(-9) \][/tex]
[tex]\[ \text{Discriminant} = 144 - 360 \][/tex]
[tex]\[ \text{Discriminant} = -216 \][/tex]
Since the discriminant is negative ([tex]\(-216\)[/tex]), the roots will be complex numbers.
Next, we calculate the roots using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\text{Discriminant}}}{2a} \][/tex]
Substitute [tex]\(b\)[/tex], the discriminant, and [tex]\(a\)[/tex]:
[tex]\[ x = \frac{-12 \pm \sqrt{-216}}{2(-10)} \][/tex]
First, simplify [tex]\(\sqrt{-216}\)[/tex]:
[tex]\[ \sqrt{-216} = \sqrt{-1 \cdot 216} = i\sqrt{216} = i\sqrt{36 \cdot 6} = i \cdot 6 \cdot \sqrt{6} = 6i\sqrt{6} \][/tex]
Now we need to put it back into the formula:
[tex]\[ x = \frac{-12 \pm 6i\sqrt{6}}{-20} \][/tex]
Simplify the fractions by dividing the terms by the common factor:
[tex]\[ x = \frac{-12}{-20} \pm \frac{6i\sqrt{6}}{-20} \][/tex]
[tex]\[ x = \frac{3}{5} \pm \frac{3i\sqrt{6}}{10} \][/tex]
Thus, the roots of the equation [tex]\(-10x^2 + 12x - 9 = 0\)[/tex] are:
[tex]\[ x = \frac{3}{5} \pm \frac{3i\sqrt{6}}{10} \][/tex]
Therefore, the correct answer is:
A. [tex]\(\boxed{x = \frac{3}{5} \pm \frac{3 i \sqrt{6}}{10}}\)[/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a = -10\)[/tex], [tex]\(b = 12\)[/tex], and [tex]\(c = -9\)[/tex].
First, we calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \text{Discriminant} = 12^2 - 4(-10)(-9) \][/tex]
[tex]\[ \text{Discriminant} = 144 - 360 \][/tex]
[tex]\[ \text{Discriminant} = -216 \][/tex]
Since the discriminant is negative ([tex]\(-216\)[/tex]), the roots will be complex numbers.
Next, we calculate the roots using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\text{Discriminant}}}{2a} \][/tex]
Substitute [tex]\(b\)[/tex], the discriminant, and [tex]\(a\)[/tex]:
[tex]\[ x = \frac{-12 \pm \sqrt{-216}}{2(-10)} \][/tex]
First, simplify [tex]\(\sqrt{-216}\)[/tex]:
[tex]\[ \sqrt{-216} = \sqrt{-1 \cdot 216} = i\sqrt{216} = i\sqrt{36 \cdot 6} = i \cdot 6 \cdot \sqrt{6} = 6i\sqrt{6} \][/tex]
Now we need to put it back into the formula:
[tex]\[ x = \frac{-12 \pm 6i\sqrt{6}}{-20} \][/tex]
Simplify the fractions by dividing the terms by the common factor:
[tex]\[ x = \frac{-12}{-20} \pm \frac{6i\sqrt{6}}{-20} \][/tex]
[tex]\[ x = \frac{3}{5} \pm \frac{3i\sqrt{6}}{10} \][/tex]
Thus, the roots of the equation [tex]\(-10x^2 + 12x - 9 = 0\)[/tex] are:
[tex]\[ x = \frac{3}{5} \pm \frac{3i\sqrt{6}}{10} \][/tex]
Therefore, the correct answer is:
A. [tex]\(\boxed{x = \frac{3}{5} \pm \frac{3 i \sqrt{6}}{10}}\)[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.